Fundamentals of Entrepreneurship (ENT 300) PC SMITH computer store / Muhammad Saifullah Sundilela … [et al.] - Sundilela, Muhammad Saifullah; Johan, Ahmad Khairil; Mohd Razi, Muhammad Alif Fikri; Azman, Muhammad Adib Danial; Muhammad Ismayuja, Muhammad Isyraf (2021)
PC SMITH is a partnership company located at Jalan Setia Gemilang in Shah Alam, Selangor. This company is a start-up business venture developed by 5 individuals for the purpose of making our own computer store. Our business is to sell a variety and type of computer parts such as graphic card, processor, ram, etc and also computer equipment such as headset, mouse, monitor etc. Our business will be promised to give an affordable price with expensive quality. We also could recommend and guide our customers in order to achieve their computer setup with the best quality based on their budget. To ensure our business success in the long term we will make sure our servers are satisfied by the customers so that they can leave our store with their computer setup happily and give many good reviews. In order to maintain our business sales in the pandemic of covid-19 that affected many businesses nowadays, we also run our business online so that customers can buy our product on our website which is www.pcsmith.com.my while quarantined at home. PC SMITH provided a delivery service, customers just chose their product and we sent the item at their front door. Being the best means providing outstanding quality, service, and value, so that our customers will be satisfied. Before the business started, we did a survey of our competitor in Setia Alam. The survey shows that our company will be up against two or more businesses that offer the same product as ours. Their business will prove to be a challenge to our company as they have been operating for years and have quite a number of loyal customers. Nevertheless, we believe with our quality services, affordable pricing and consistency will go beyond them and reach customers' requirements, needs and wants. In the future, we are expecting that our business will create many upcoming innovations, creativity and services in order to become a successful business